2023
DOI: 10.1093/jcag/gwad021
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity for Quiescent and Mildly Active Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis

Banke Oketola,
Olayinka Akinrolie,
Sandra Webber
et al.

Abstract: Background Physical activity (PA) may benefit people with inflammatory bowel diseases (IBD) by improving immunological response, musculoskeletal function, and psychological health. Aims We distilled available evidence on the efficacy and safety of PA to improve health-related quality of life (HRQoL) and relieve persistent symptoms of fatigue, joint pain, abdominal pain, stress, anxiety, and depression in individuals with quie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Of these therapies, cognitive-behavioral therapy was most effective, but the effect was not statistically significant possibly because of small sample sizes. The role of physical activity interventions in improving fatigue also remains uncertain (50). However, adaptive health behaviors such as optimization of diet, exercise, and sleep from a behavioral medicine approach may be beneficial (51).…”
Section: Discussionmentioning
confidence: 99%
“…Of these therapies, cognitive-behavioral therapy was most effective, but the effect was not statistically significant possibly because of small sample sizes. The role of physical activity interventions in improving fatigue also remains uncertain (50). However, adaptive health behaviors such as optimization of diet, exercise, and sleep from a behavioral medicine approach may be beneficial (51).…”
Section: Discussionmentioning
confidence: 99%
“…15 Multiple studies have demonstrated the positive impact of exercise on fatigue in individuals with IBD. [16][17][18] However, following an IBD diagnosis, patients tend to engage in significantly less physical activity (PA). 19 Moreover, there is limited research on the intensity of PA and levels of fatigue in IBD patients with varying levels of disease activity, 20 and many controversial aspects still exist.…”
Section: Introductionmentioning
confidence: 99%